Effect Of Genetic And Non-Genetic Factors On Lactation Yield In Malvi Cows - Sharma, Harish; Tomar, S.S.; Kumar , Amit (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
The data for the present investigation pertained to 1647 observations of lactation yield (LY) on Malvi cows maintained at Govt. Cattle Breeding Farm, Agar, District Shajapur (M.P.), covering a period of 48 years from 1962 to 2009. The least squares analysis of variance revealed the mean LY in these cows to be 854.90±33.52 kg and the trait was significantly affected by sire (P< 0.01), period (P< 0.01), parity (P< 0.01) and inbreeding (P< 0.05). Heritability estimates for LY was obtained as 0.16±0.13. It was inferred that inbreeding had deteriorating effect on the lactation yield and hence to improve the lactation yield in this herd, avoidance of inbreeding along with ameliorative managerial practices should be adopted.
Keywords: Malvi cows; inbreeding; lactation yield; heritability